Predicting toxic heavy metal movements in upper Sanyati catchment in the midlands province in Zimbabwe - Madebwe, Victor; Munodawafa, Adelaide; Mugabe, Francis T.; Madebwe, Crescentia (2016)
The study assessed toxic heavy metal concentrations in the upper Sanyati catchment in the Midlands Province in Zimbabwe and predicted their movements and potential impacts on ground water quality. Topographic surveying was used to determine borehole locations, elevations, hydraulic conductivity and water yields. Monthly ground water samples were analyzed to determine concentrations of Cr, Pb, Cd and Ni for a period of two-years. The results obtained for the wet season showed mean concentration levels of Cr, Pb, Cd and Ni at 0.25, 0.015, 0.042 and 0.031mg/L respectively. Dry season mean concentration levels for Cr, Pb, Cd and Ni were 0.15, 0.07, 0.06 and 0.025 mg/L respectively. Water samples from boreholes located in areas where mining, mineral processing and agricultural activities were dominant, yielded the highest values of toxic heavy metals. Dilution Attenuation Factor (DAF) for each toxic heavy metal was calculated to observe metal behaviour along the contaminant path for each season. The results showed seasonal variation in the spatial distribution of each toxic heavy metal during the wet season between October to March and during the dry season between April to September. Overall, research results showed that concentrations of Cr, Pb, Cd and Ni were above the standard limits set by the World Health Organization.